Shock waves in relativistic gas - B. V. Alekseyev; V. V. Mikhaylov; I. V. Ovchinnikova (Тонкие химические технологии)
The problem of shock waves propagation in ultra-relativistic media is considered. A system of transport equations for shock waves is obtained on the basis of the non-local relativistic hydrodynamic theory. Numerical solution of these equations is applied for analyzing the structure of the transition layer using different boundary conditions.